Interrogating Colonial Legacy of Active Learning Strategies in English Language Education: A Postcolonial Critique - Thapa, Deepak (KMC Journal, 2026)
Linguistic imperialism continues to persist unintentionally through pedagogical practices, even within contemporary decolonial contexts. Drawing insights from postcolonial theoretical lens, this thematic paper critically interrogates the colonial legacy embedded within Nepalese English language classrooms. I adopted Braun and Clarke’s thematic literature review as a theoretical framework to identify recurring pattern and themes from the existing literature around my study area of the western dominance in the adoption of pedagogical approaches in the non-western contexts. For the study purpose, secondary sources were used to critique on the issue. Using Google database search engine as the data source, I collected only eight relevant academic papers strictly following the systematic literature review process. Furthermore, four books were purposively selected to respond to the search questions. The findings of the study revealed that teaching approaches developed in monolingual context, still dominates significantly even within the post-colonial context. This study highlights the importance of developing culturally relevant active learning teaching approaches to resist the western legacy, arguing that uncritically adopted methods in multilingual and multicultural contexts like ours, reinforces the unintentional western legacies to non-western unique educational settings. This study is significant because it serves as an instrumental tool for policy makers and academic leaders to strategically adapt the western centric teaching approaches and focus more on culturally sensitive pedagogical approaches in multilingual and multicultural classrooms within post-colonial settings.